The impossible lives of Greta Wells [large type] - Greer, Andrew Sean (Center Point Large Print, 2013)
After the death of her beloved twin brother and the abandonment of her long-time lover, Greta Wells undergoes electroshock therapy. Over the course of the treatment, Greta finds herself repeatedly sent to 1918, 1941, and back to the present. Greta is fascinated by her alter egos: in 1941, she is a devoted mother; in 1918, she is a bohemian adulteress. Separated by time and social mores, Greta's lives are achingly similar, fraught with familiar tensions and difficult choices. Each reality has its own losses, its own rewards, and each extracts a different price. And the modern Greta learns that her alternate selves are unpredictable, driven by their own desires and needs. As her final treatment looms, questions arise. What will happen once each Greta learns how to stay in one of the other worlds? Who will choose to remain in which life?